The histone methyltransferase Wolf–Hirschhorn syndrome candidate 1‐like 1 (WHSC1L1) is involved in human carcinogenesis. Issue 2 (25th September 2012) - Kang, Daechun; Cho, Hyun‐Soo; Toyokawa, Gouji; Kogure, Masaharu; Yamane, Yuka; Iwai, Yukiko; Hayami, Shinya; Tsunoda, Tatsuhiko; Field, Helen I.; Matsuda, Koichi; Neal, David E.; Ponder, Bruce A. J.; et al.
Abstract: Histone lysine methylation plays a fundamental role in chromatin organization. Although a set of histone methyltransferases have been identified and biochemically characterized, the pathological roles of their dysfunction in human cancers are still not well understood. In this study, we demonstrate important roles of WHSC1L1 in human carcinogenesis. Expression levels of WHSC1L1 transcript were significantly elevated in various human cancers including bladder carcinoma. Immunohistochemical analysis of bladder, lung, and liver cancers confirmed overexpression of WHSC1L1. WHSC1L1 ‐specific small interfering RNAs significantly knocked down its expression and resulted in suppression of proliferation of bladder and lung cancer cell lines. WHSC1L1 knockdown induced cell cycle arrest at the G2 /M phase followed by multinucleation of cancer cells. Expression profile analysis using Affymetrix GeneChip ® showed that WHSC1L1 affected the expression of a number of genes including CCNG1 and NEK7, which are known to play crucial roles in the cell cycle progression at mitosis. As WHSC1L1 expression is significantly low in various normal tissues including vital organs, WHSC1L1 could be a good candidate molecule for development of novel treatment for various types of cancer. © 2012 Wiley Periodicals, Inc.